Construction and Characterization of an Intergeneric Fusant That Degrades the Fungicides Chlorothalonil and Carbendazim - Xue, Chen; Zheng, Jiaxin; Wang, Guangli; Feng, Liang; Li, Feng (Frontiers in Microbiology, 2022)
Bordetella sp. CTN-16 (GenBank FJ598326) can degrade chlorothalonil (CTN) but not carbendazim (MBC), and Microbacterium sp. MBC-3 (GenBank OK667229) can degrade MBC but not CTN. A functional strain BD2 was obtained by protoplast fusion of CTN-16 and MBC-3 to generate a fusant with improved degradation efficiency of CTN and MBC simultaneously. Fusant-BD2 with eighth transfer on a medium containing CTN and two antibiotics was obtained. To identify and confirm the genetic relationship between parental strains and fusion strain BD2, scanning electron microscopy (SEM), randomly amplified polymorphic DNA (RAPD), and 16S ribosomal RNA (rRNA) gene sequences analysis were carried out. SEM analysis illustrated BD2 and its parents had some slight differences in the cell morphology. Fusant-BD2 not only possessed the same bands as parental strains but also had its specific bands analyzed through RAPD. The genetic similarity indices for BD2 and its parental strains CTN-16 and MBC-3 are 0.571 and 0.428 respectively. The degradation rates of CTN and MBC were 79.8% and 65.2% in the inorganic salt solution containing 50 mgL-1 CTN and 50 mgL-1 MBC, respectively, and the degradation efficiencies were better than the parental strains CTN-16 and MBC-3. This study provides a prospect for the application of fusion strain BD2 in bioremediation of CTN and MBC contaminated sites.